2021
DOI: 10.1089/brain.2020.0879
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Changes in Hippocampal Interneurons Subtypes in the Pathogenesis of Alzheimer's Disease: A Systematic Review

Abstract: Background: It is becoming increasingly recognized that there is significant interneuron degeneration in Alzheimer's disease. As the hippocampus is integral for learning and memory, we performed a systematic review of primary literature focused on the relationship between Alzheimer's and hippocampal interneurons. In this study, we summarize the experimental work performed to date and identify opportunities for future experiments. Objectives: This PRISMA (Preferred Reporting Items for Systematic Reviews and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 88 publications
(201 reference statements)
0
11
0
Order By: Relevance
“…ADassociated hyperexcitability is thought to spread the disease pathology between brain subregions (Khan et al, 2014;Petrache et al, 2019). The process by which this develops remains to be fully answered, with one hypothesis referring to the selective aberrant behaviour of inhibitory neurotransmitter GABA-containing interneurons (Rice et al, 2020;Shi et al, 2020;Xu et al, 2020;Reid et al, 2021), despite an elevated background inhibition observed in AD by others (Jo et al, 2014;Wu et al, 2014). Surprisingly, the levels of astrocyte glutamate decarboxylase 67 (GAD67), an enzyme that converts glutamate to GABA, is shown to be elevated in astrocytes in AD patients and mouse models of AD (Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…ADassociated hyperexcitability is thought to spread the disease pathology between brain subregions (Khan et al, 2014;Petrache et al, 2019). The process by which this develops remains to be fully answered, with one hypothesis referring to the selective aberrant behaviour of inhibitory neurotransmitter GABA-containing interneurons (Rice et al, 2020;Shi et al, 2020;Xu et al, 2020;Reid et al, 2021), despite an elevated background inhibition observed in AD by others (Jo et al, 2014;Wu et al, 2014). Surprisingly, the levels of astrocyte glutamate decarboxylase 67 (GAD67), an enzyme that converts glutamate to GABA, is shown to be elevated in astrocytes in AD patients and mouse models of AD (Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer’s disease (AD) is a progressive neurodegenerative disorder, and one of the most common causes of dementia. Although the underlying mechanisms of AD are still not completely understood, disrupted interneuron function has been associated with AD ( Reid et al, 2021 ). For example, accumulation of the amyloid-β (Aβ) protein, which is a classical hallmark of AD pathology, has been shown to alter excitatory/inhibitory balance; this aspect of disease pathology is implicated in the observed learning and memory deficits associated with AD ( Verret et al, 2012 ; Palop and Mucke, 2016 ; Hijazi et al, 2020 ).…”
Section: Brain State-regulated Interneuron Functions In Brain Disordersmentioning
confidence: 99%
“…For example, accumulation of the amyloid-β (Aβ) protein, which is a classical hallmark of AD pathology, has been shown to alter excitatory/inhibitory balance; this aspect of disease pathology is implicated in the observed learning and memory deficits associated with AD ( Verret et al, 2012 ; Palop and Mucke, 2016 ; Hijazi et al, 2020 ). Recent work in AD mouse models has found either decreased, unchanged, or increased PV+ cell density in CA1 ( Hollnagel et al, 2019 ; Reid et al, 2021 ). The differences in findings are likely explained in part by differences between various transgenic AD mouse models and the age at which mice are examined in different studies ( Ruden et al, 2021 ).…”
Section: Brain State-regulated Interneuron Functions In Brain Disordersmentioning
confidence: 99%
See 2 more Smart Citations